Asymmetric loss of parietal activity causes spatial bias in prodromal and mild Alzheimer's disease - Sorg, Christian; Myers, Nicholas; Redel, Petra; Bublak, Peter; Riedl, Valentin; Manoliu, Andrei; Perneczky, Robert; Grimmer, Timo; Kurz, Alexander; Foerstl, Hans; Drzezga, Alexander; Mueller, Hermann J.; et al. (Biological Psychiatry, 2012)
Background: In Alzheimer's disease (AD), loss of effective neuronal activity is reflected by cortical glucose hypometabolism. Hypometabolism in the posterior parietal cortex (PPC) is among the first in vivo signs of AD; however, its functional impact on large-scale brain mechanisms and behavior is poorly understood. The lateral PPC contributes to spatial attention constituting a basic function of the human brain. We hypothesized 1) that lateral PPC hypometabolism is associated with impaired spatial attention in very early AD and 2) that impaired competition of effective neuronal activity across hemispheres might underlie this deficit in terms of brain mechanisms. Methods: A model-based imaging approach was applied to assess patients with prodromal (n = 28) and mild (n = 7) AD. Quantitative attention parameters, derived from performance on simple psychophysical tasks and analyzed by Bundesen's computational theory of visual attention, were related to brain metabolism, measured by 18F-fluorodeoxyglucose positron emission tomography. Results: Patients' left and right lateral PPC metabolism was reduced. Nine patients had significant spatial attentional bias on the left side and two patients on the right. Direction and degree of spatial bias was correlated with direction and degree of an interhemispheric metabolism bias in the inferior parietal lobe and temporoparietal junction. Conclusions: Our data provide evidence that in very early AD, asymmetric hypometabolism of the lateral PPC causes spatial attentional bias. Results are broadly consistent with the model that asymmetrically impaired effective neuronal PPC activity in AD biases the competition of visual objects for cortical representation and access to awareness to one side. © 2012 Society of Biological Psychiatry.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Bundesen's theory of visual attention; FDG-PET; model-based imaging; parietal cortex; prodromal Alzheimer's disease; spatial attention